2005
DOI: 10.1016/j.ymthe.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ECM–Integrin Interaction with Liposome-Encapsulated Small Interfering RNAs Inhibits the Growth of Human Prostate Cancer in a Bone Xenograft Imaging Model

Abstract: The intricate intracellular communication between stromal and epithelial cells, which involves cell-cell-, cell-insoluble extracellular matrix- (ECM), and cell-soluble factor-mediated signaling processes, is an attractive target for therapeutic intervention in hormone-refractory and bone-metastatic prostate cancer. In the present study we demonstrated that androgen-independent PC3 prostate cancer cells adhered to and migrated on vitronectin (VN), a major noncollagenous ECM in mature bone, through the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 35 publications
1
59
0
Order By: Relevance
“…40,41 In one study using siRNA, a soil-dependent effect was observed. Bisanz et al 18 reported a strong effect of siRNA directed against integrin subunits combined with liposome on the growth of human prostate tumor in bone, but not on subcutaneaous tumor growth. Similar site-dependent effects can be expected with siRNA directed against RANKL, the major cytokine involved in the vicious cycle between osteolysis and bone tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 In one study using siRNA, a soil-dependent effect was observed. Bisanz et al 18 reported a strong effect of siRNA directed against integrin subunits combined with liposome on the growth of human prostate tumor in bone, but not on subcutaneaous tumor growth. Similar site-dependent effects can be expected with siRNA directed against RANKL, the major cytokine involved in the vicious cycle between osteolysis and bone tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies have predominantly decreased the expression of genes associated with cell cycle. [18][19][20][21] In osteosarcomas, one way to evaluate the therapeutic potential of small interfering RNA (siRNA) would be to target expression of RANKL in comparison with its blockage by antibody. However, the main challenge for the successful use of siRNA in vivo is to achieve an efficient delivery of these molecules to the target tissue without off-target effects.…”
Section: Introductionmentioning
confidence: 99%
“…Bisanz et al (32) have illustrated a positive role of a v integrins on prostate tumor survival in the bone. Integrin a v b 3 activation on tumor cells is essential for the recognition of key bone-specific matrix proteins, suggesting that the a v b 3 integrin modulates prostate cancer growth in distant metastasis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo studies also support the view. For instance, intratumoral administration of liposome-encapsulated human α v -siRNA significantly inhibits the growth of PC-3 prostate tumor cells in skeleton, which was associated with decreased integrin α v subunit expression and increased apoptosis in tumor cells [106]. Another recent mouse model study demonstrated that the expression of fully functional α v β 3 promoted tumor growth in bone, whereas inactive mutants failed to do so [104], further suggesting that integrin α v β 3 may play a role in prostate cancer cell-bone interaction.…”
Section: Prostate Cancer-bone Interactionmentioning
confidence: 99%